Incorporating Traditional Arts and Crafts in Visual Arts Education: Enhancing Creativity and Cultural Awareness - Raxmonova Mahliyo Zoir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the pedagogical value of integrating traditional arts and crafts into visual arts education. It examines how using national crafts, textile patterns, and decorative motifs in lessons fosters students’ creative thinking, aesthetic development, and appreciation of cultural heritage. The paper also discusses effective strategies for incorporating traditional arts into contemporary classroom practices.